Exploring the interplay between HIV and AIDS treatment discourses and subjectivity in South Africa - Nkomo, Nkululeko (My University, 2017)
This thesis explores the rearticulation of subjectivity in the context of the struggle for antiretroviral therapy in South Africa, and also in the contemporary era of treatment accessibility for HIV and AIDS. Two sub-aims are investigated: the first concerns exploring how, and with what consequences, subjectivity was deployed in the contestations that characterized the South African ‘AIDS war’; the second concerns inquiring into the intelligibility of subjectivity in public and everyday consciousness in the post-AIDS war period. Integrating qualitative analyses with the theoretical lens of an analytics of governmentality, the data set includes policy-related archival materials, a popular HIV advice column and interviews with people living with HIV and on antiretroviral therapy. The thesis brings into sharp focus the adumbration of the right to health with rational decision-making, dignity and autonomy. Much more than a way of organizing interests, advocating for the right to treatment - to prevent the transmission of HIV from mother to child and to slow-down HIV spread - was a strategy of effecting a rationality-cum-affective transfiguration of a widespread helplessness and despair into self-reliance and hope. At the level of public and everyday consciousness, self-government on antiretroviral therapy lies at the intersection of knowledge, self-care and self-management. However, such a subjective positionality is not adopted unproblematically, or even sustained indefinitely, owing to the relative weight of other disparate requirements upon oneself from day to day. What emerged out of the epic battle for antiretroviral therapy, undergirding the prevailing current public and policy orientation to antiretroviral therapy care, was the combination of an optimistic rationality and a hopeful affectivity for the potential of fashioning an HIV-positive subjectivity, contiguously responsibilized and self-responsibilizing. At the experiential level of living on ARVs, where autonomy is synonymous with self-regulation, the thesis demonstrates that self-responsibility is also an unpredictable and fluid undertaking of navigating the affective tumult of hopefulness, uncertainty, sacrifice and tension.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy, July, 2017
Keywords: AIDS (Disease)--Social aspects--South Africa; HIV infections--Social aspects--South Africa; AIDS (Disease)--Treatment--South Africa